Nearly 3,000 salivary stones: some clinical and epidemiologic aspects - Sigismund, Paolo E.; Zenk, Johannes; Koch, Michael; Schapher, Mirco; Rudes, Mihael; Iro, Heinrich (Laryngoscope, 2015)
To investigate epidemiological features and symptoms of sialolithiasis and their implications for diagnosis and management.Retrospective cohort study.Retrospective analysis on 2,322 patients with sialolithiasis, between 1987 and 2009. The statistical significance between two sample distributions was computed using analysis of variance Student t test for two-tailed distribution.A total of 2,959 calculi were identified by means of ultrasound. Of those, 80.4% were located in the submandibular duct system (53% hilar/proximal, 37% distal, 10% intraparenchymal) and 19.6% were parotid stones (83% in Stensen's duct, 17% intraparenchymal). Sialoliths had been discovered beforehand in the submandibular gland (P = 0.00024; t test). Symptoms, measured from first visit, lasted on average 26 months (range: 1 day-30 years). The main group suffered from swelling (50.3%), followed by painful swelling (41.6%) and pain (3.1%). Multiple stones were found in 16.9% of patients (18.1% in the submandibular gland; 14.3% in the parotid). Average stone diameter in the submandibular gland was 8.3 mm (range 1-35 mm), and the stones were in Lustmann group II (46%). In the parotid gland, the average diameter was 6.4 mm (range 1-31 mm), and 51% were in Lustmann group I.Nowadays, epidemiologic features and clinical manifestations of sialolithiasis play an important role, assisting not only in diagnosis but also in determining appropriate treatment. Due to their location and smaller diameter, parotid stones in some cases can only be treated using a mini-invasive endoscopic technique. Submandibular stones more often require a combined approach.4
EVALuna2:19993